An enzyme cascade sensor with resistance to the inherent intermediate product by logic-controlled peroxidase mimic catalysis. Issue 16 (29th January 2021) - Yu, Renzhong; Wang, Rui; Wang, Zhaoyin; Liu, Bo; He, Xue; Dai, Zhihui
Abstract : A colorimetric enzyme cascade detection strategy with resistance to the inherent intermediate product was reported based on logic-controlled activation of the peroxidase mimic sensing system. Abstract : Enzyme cascade sensors usually could not discriminate between the target and intermediate product. Herein, based on "AND" logic-controlled activation of the glucose oxidase–copper peroxide sensing system, enzyme cascade detection for glucose with resistance to inherently existing intermediate product H2 O2 was reported for the first time, which may provide a novel way for facilitating enzyme cascade sensing.